The effects of a 4-week, intensified training, and competition period on salivary hormones, immunoglobulin A, illness symptoms, and mood state in elite synchronised swimmers - Tanner, A.; Day, S. (Sports, 2017)
Given the limited research into the physiological and psychological demands of elite synchronised swimming, the aim of this study was to examine 10 elite female synchronised swimmers and analyse the relationship between training load, stress, illness episodes, and salivary biomarkers during a period of training and competition. Saliva samples were collected before (BASE), during an intensified training camp (CAMP), during an international competition period (COMP), and post competition recovery (REC) for analysis of cortisol, testosterone, and secretory immunoglobulin A (SIgA). Illness symptoms, Daily Analysis of Life Demands of Athletes (DALDA), and training load were also monitored. Training load significantly increased from BASE during CAMP and COMP (p < 0.01), and SIgA secretion was higher during COMP compared to BASE and CAMP (p < 0.01). There was no change in salivary testosterone; however, salivary cortisol was elevated during COMP compared to BASE (93%, p < 0.05). DALDA `a scores` were correlated with salivary cortisol (r = 0.429, p = 0.0001). The study demonstrates that a short period of intensified training and competition did not have a detrimental effect on mucosal immunity in elite synchronised swimmers; however, swimmers displayed higher cortisol levels during the competition and increased stress symptoms.